1999
DOI: 10.1111/j.1600-0560.1999.tb01797.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo abnormal keratinization in Darier‐White's disease as viewed by real‐time confocal imaging

Abstract: Darier-White's disease is a rare autosomal-dominant disorder of keratinization. The underlying pathology for the clinical presentation is acantholysis, and various types of dyskeratosis and acanthosis. In this study, we utilized a non-invasive optical imaging modality, confocal reflectance microscopy, to identify specific histologic features of Darier-White's disease in vivo. Micrographic findings in the confocal images were corps ronds, suprabasal clefts, acantholytic suprabasal keratinocytes, and villi. Real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…Further, well-established histological features of psoriasis and other inflammatory skin lesions can be visualized with this technique, including characteristic PMN accumulations. It has been shown that these RCM images correlated highly with histology (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 95%
“…Further, well-established histological features of psoriasis and other inflammatory skin lesions can be visualized with this technique, including characteristic PMN accumulations. It has been shown that these RCM images correlated highly with histology (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 95%
“…González et al [14] presented confocal images of dyskeratosis in the form of 7-10 µm cells in the stratum corneum, some of them containing a pyknotic nucleus, called Darier's grains. Below the stratum corneum the so-called 'corps ronds' 20-25 µm in diameter were found.…”
Section: Darier's Diseasementioning
confidence: 99%
“…Studies comparing and identifying structures imaged by conventional histological sectioning and the confocal laser scanning microscopy are available [15][16][17][18]. The microscope used in this study consisted of a light source, pin holes, a movable lens, a beam splitter and a photo detector.…”
Section: Study Design Of the Determination Of The Number Of Dermal Pamentioning
confidence: 99%